(untitled) (Advancements in Homeopathic Research, 2022)
This clinical observational study was carried out to ascertain the effects of different potencies of Hydrangia Arborescens including mother tincture in Renal Calculi of various sizes. In this study 87 clinical cases were taken. Clinical cases with positive urine and USG reports were included in this study of over two year. It was seen that middle age group patients are more affected by the Renal Calculi due to their lifestyle. Hence Renal Calculi is common in people aged from 20 to 60 years. It was also seen through the study that Hydrangia Arborescens was the beneficial remedy in various potencies including mother tincture. And also it was seen through the study that within few months most of the cases were treated successfully and hence there is a vast scope for Hydrangia Arborescens in Renal Calculi. The overall results shows that in 78 cases there was good improvement and its percentage is 89.66% and in 04 cases there was partial improvement and its percentage is 04.60 % and in 05 cases there was no improvement and its percentage is 05.75%. The efficacy of Hydrangia Arborescens in the treatment of Renal Calculi is excellent and shows high success rate. There were no complications in the 87 patients seen in this study. It is also necessary to understand causes of Renal Calculi and practices to prevent them. This research work will lead to further reduction in the use of harmful conventional therapy, lithotripsy and surgical intervention in Renal Calculi, as Hydrangia Arborescens works as a stone breaking remedy.